Logarítmos: uma proposta de ensino - Reis, Saulo Portes dos [UNESP] (2014)
This paper presents a proposal for teaching the concept of logarithms from the historical context of its evolution. Two perspectives are addressed: the origin of logarithms motivated by the need to simplify calculations; the use of logarithmic relationship to calculate the area of a zone hyp erbole. Our main goal is that the teacher high school understand the logarithms, that although not calculations simplify (nowadays), understanding this concept becomes important by presenting others properties